2015
DOI: 10.1002/jemt.22603
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Sheath/Core nanofibers containing olive leaf extract

Abstract: This study aimed at producing silk fibroin (SF)/hyaluronic acid (HA) and olive leaf extract (OLE) nanofibers with sheath/core morphology by coaxial electrospinning method, determining their antimicrobial properties, and examining release profiles of OLE from these coaxial nanofibers. Optimum electrospinning process and solution parameters were determined to obtain uniform and bead-free coaxial nanofibers. Scanning electron microscopy and transmission electron microscopy (TEM) were used to characterize the morp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 44 publications
0
18
0
1
Order By: Relevance
“…12 It was reported that olive leaf extract was successfully encapsulated into coaxial silk broin/hyaluronic acid nano-bers, which exhibited favourable antibacterial properties and release stability. 13 Lópezrubio et al found that coaxial electrospinning was a more efficient method to entrap living bidobacteria cells and improve their viability compared with single electrospinning. 14 Zein is the major storage protein of corn, and has extensive application in encapsulation of bioactive substances.…”
Section: Introductionmentioning
confidence: 99%
“…12 It was reported that olive leaf extract was successfully encapsulated into coaxial silk broin/hyaluronic acid nano-bers, which exhibited favourable antibacterial properties and release stability. 13 Lópezrubio et al found that coaxial electrospinning was a more efficient method to entrap living bidobacteria cells and improve their viability compared with single electrospinning. 14 Zein is the major storage protein of corn, and has extensive application in encapsulation of bioactive substances.…”
Section: Introductionmentioning
confidence: 99%
“…The hydrolysis of oleuropein into hydroxytrosol and its derivatives helped the enhancement of the antibacterial activity of the olive leave extract having oleuropein as main constituent. Antimicrobial activity of oleuropein and hydroxytyrosol were also reported in the literature[23,24]. Hydroxytyrosol has higher antimicrobial activity compared with that of oleuropein.…”
mentioning
confidence: 57%
“…Among these techniques, electrospinning is usually preferred as it allows versatility in the control of the size of nanofibers, convenience for scaleup, and flexibility in terms of the materials used for nanofiber production [5]. Different biopolymers, such as collagen, silk fibroin, hyaluronic acid, and zein can be used to prepare nanofibers by electrospinning [2,6,7]. The silk fibroin used in this study is an important natural biopolymer and has been used to prepare electro-spun nanofibers that are used in many biotechnological applications such as in medical textiles, drug delivery and tissue scaffolding [8].…”
Section: Introductionmentioning
confidence: 99%
“…However, less toxic, naturally occurring antimicrobial agents are still needed for biotechnological applications. Recently, nanofibers incorporating bioactive natural compounds have received much attention for biomedical and tissue engineering applications [5,6]. There is intense interest in the use of plant-derived natural compounds having different bioactivities for many biotechnological applications [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation